Butyric acid production with high selectivity coupled with acetic acid consumption in sugar-glycerol mixture fermentation by Clostridium tyrobutyricum ATCC25755 - Oh, Hyun Ju; Kim, Ki-Yeon; Lee, Kyung Min; Lee, Sun-Mi; Gong, Gyeongtaek; Oh, Min-Kyu; Um, Youngsoon (Journal of industrial and engineering chemistry (Seoul, Korea), 2019)
[Display omitted] •Butyric acid production was investigated using glucose–glycerol mixture.•Glycerol was not consumed without acetic acid by Clostridium tyrobutyricum.•Acetate consumption and reassimilation were observed in sugar–glycerol fermentation.•High butyric acid selectivity was achieved through acetic acid consumption.•It is the first report on glycerol consumption-involved butyric acid production. Butyric acid-producing strain Clostridium tyrobutyricum ATCC25755 produces acetic acid as a byproduct, which lowers butyric acid yield and selectivity. Supplementing glycerol would be a rational approach to enhance a NADH-requiring metabolite butyric acid selectivity by increasing NADH availability; however, there has been no report butyric acid production using glycerol as either a sole carbon source or a co-substrate with C. tyrobutyricum. In this study, glycerol was supplemented along with sugar to increase NADH availability facilitating the production of butyric acid. C. tyrobutyricum was found to simultaneously consume glucose and glycerol only when acetic acid was present. Notably, acetic acid was not produced but consumed. The amount of glycerol consumption was linearly dependent on the amount of acetic acid consumption. When mixed sugars (glucose 80 g/L and xylose 30 g/L) and crude glycerol were used, not only exogenous acetic acid consumption but also acetic acid reassimilation were clearly observed, resulting in significantly enhanced butyric acid production (54.79 g/L), yield (0.464 g/g), and selectivity (98.3%) compared to sugar-only fermentation (production, 35.42 g/L; yield, 0.339 g/g; selectivity, 69.1%). Therefore, this study would pave the way for selective and cost-effective butyric acid production using sugars and glycerol from biodiesel facility.